An Empirical Study for Green Transportation Scheme of Municipal Solid Waste Based on Complex Data Model Analysis. (8th April 2021) - Xin, Chunlin; Wang, Lingjie; Liu, Bin; Yuan, Yu-Hsi; Tsai, Sang-Bing
Abstract : Solid waste management and air pollution are two pressing issues in the functioning of large cities. This paper studies the optimization problem of the green transportation route of municipal solid waste and establishes a mathematical planning model based on real-time traffic conditions of the city and consideration of a time window and multiple transfer stations with the goal of minimizing energy consumption. In the optimal green transportation process in this paper, comprehensive consideration of vehicle speed, vehicle load, road gradient, and driving distance in different road sections based on real-time traffic conditions is incorporated, which has a better fuel-saving potential than the shortest path. A green transportation program can alleviate the air pollution problem in big cities and promote energy conservation and emission reduction in solid waste transportation.